Association of Fundus Autofluorescence Findings and Outer Retinal Lesions on Optical Coherence Tomography With Visual Acuity in Birdshot Chorioretinopathy. (July 2019) - Kopplin, Laura J.; Munk, Marion; Baynham, Justin; Rosenbaum, James T.; Suhler, Eric B.; Biggee, Kristin; Goldstein, Debra A.; Lin, Phoebe
Purpose: This article investigates the optical coherence tomography (OCT) and fundus autofluorescence imaging findings in birdshot chorioretinopathy (BSCR) and their association with visual acuity (VA). Methods: In a retrospective, cross-sectional study, we evaluated OCT images for changes in retinal structure including cystoid macular edema (CME), epiretinal membrane, and outer retinal lesions. We assessed autofluorescence images for hypoautofluorescent and hyperautofluorescent changes and noted the distribution of the lesions. Demographic data and VA at the time of imaging were also collected. Associations between OCT and autofluorescence findings and logarithm of the minimum angle of resolution VA were tested using linear regression. Results: We conducted a chart review of 80 eyes from 40 patients with BSCR. Outer retinal lesions were found on OCT in 28 of 80 eyes (35%) and disruption of the outer segment ellipsoid zone (EZ) occurred in 23 eyes (28.7%). Macular hypoautofluorescent lesions were more common than hyperautofluorescent lesions, present in 58.8% and 13% of eyes, respectively. The presence of outer retinal lesions on OCT was significantly associated with reduced VA ( P = .006) as was EZ disruption ( P = .003). These associations remained significant after accounting for the presence of macular edema. There was a trend toward association of macular hypoautofluorescent lesions with decreased vision, although it was not statistically significant ( P = .17). Conclusions: The association of outer retinal lesions with decreased VA suggests a mechanism of central vision loss that is distinct from CME and may provide an additional objective finding to monitor disease activity in BSCR patients.